Investigation of the potential to improve DC fast charging station economics by integrating photovoltaic power generation and/or local battery energy storage system. (15th January 2019) - Yang, Libing; Ribberink, Hajo
Abstract: The economic feasibility of DC Fast Charging (DCFC) stations is strongly impacted by electricity charges, billed by electricity consumption (kWh) and power demand (kW), that have to be paid to the local utility. In this simulation study, the possibilities to significantly improve DCFC economics by reducing these utility charges have been investigated for DCFC stations assumed to be installed at highway service centres in Ontario and in Alberta (Canada). Various scenarios, in which the DCFCs are complemented by local photovoltaic (PV) power generation and/or a battery energy storage system (BESS), are evaluated against a reference case with only a grid connection. The discounted payback periods of the required additional capital investments have been examined. The analysis results indicate that the proposed systems are able to reduce the demand charges due to the addition of BESS and reduce the electricity consumption charges due to the utilization of PV. Although the proposed systems cannot pay themselves back within a reasonable period under the current PV and battery prices, the economic viability in a 5- to 10-year timeframe becomes quite promising considering the expected continuous decline of these prices because of technology advancement, manufacturing efficiencies and market expansions. Highlights: Integration of PV and battery reduces electricity consumption charges and demand charges respectively. The synergy between the PV and battery energy storage is rather limited. It is more cost-effective to install the proposed systems in locations having high electricity rates. Currently, PV systems could provide marginal economic benefit, but BESS is still too costly. The proposed systems would become economically viable in 5–10 years due to price drop of PV and BESS.